Theoretical calculation of the control parameters for Beam Selection Magnet of the 30MeV Cyclotron - Tran , Van Dien (Nuclear Science and Technology, 2016)
Beam Selection Magnet (BSM) is a dipole magnet located at the end of the beamline in cyclotron 30MeV system. It performs steering proton beam from beamline to individual targets for radioisotopes production. Therefore, it plays an important role in focusing the beam onto the targets. The aim of this work is to determine its control parameters in theory based on the designed technology and theory of accelerator physics. The obtained calculation results were compared with baseline parameters that have been configured to control this system in producing of 18F and 11C radioisotopes. This work could be used as a basis for new parameters selection to control BSM if new targets are installed.